LEGAL AND ECONOMIC CONCEPTS OF THE BALANCE SHEET IN GERMANY. - Weigmann, W. (The Accounting Review, 1932)
This article describes legal and economic concepts of the balance sheet in Germany. he balance sheet is essentially a scheme for classifying property and capital, and is not vitally concerned that different amounts of property came in to the business at different dates. Therefore those who hold to these views are faced with no problems of valuation. Knowledge of current values for assets and capital is not absolutely essential to management. Although for certain purposes current values may be needed, it is more important to have a proper classification of the items of property and capital and to preserve the comparability of successive statements. A dynamic balance sheet must be supreme for the use of the manager because his decisions are dictated by his struggle for profit. The clear and concise ideas of writers who take the management point of view of accounting point out the proper course to follow. Legal requirements are obviouslyto be satisfactorily met, but the manager'svaluation problems can be best solved bythe application of economic principals.